Analysis of allocation of hand pump technology for procurement as a safe drinking water source installed by DPHE - Alom, Md. Rashidul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.